Flexural strengthening and recovery in freshwater and saline ice, 2018-2021 - Andrii Murdza; Erland Schulson; Carl Renshaw (Arctic Data Center, 2021)
Increasing fetch as sea ice retreats with global warming is increasing the amplitude of ocean waves, motivating the need for a better understanding of the impact of episodic flexing on the strength of ice. Unexpectedly, recent studies showed that the flexural strength of ice increases by as much as a factor of two or more upon both cyclic and creep loadings, possibly owing to the development of an internal back stress originating from dislocation pileups. New systematic experiments reveal that the cyclically-induced increase in flexural strength of columnar-grained S2 (S2 texture is one in which the crystallographic c-axes of the individual grains of ice are oriented perpendicular to the long axis of the columnar-shaped grains but randomly oriented within the plane normal to the long axis) freshwater and saline ice is fully recovered upon annealing at high homologues temperatures (i.e. the temperature of a material as a fraction of its melting point temperature using Kelvin scale, in our case Th=0.91 and 0.96). Moreover, the ice can be repeatedly strengthened to the same level by cyclic loading if allowed to anneal after each episode of strengthening. The recovery of the original strength is attributed to the relaxation of the cyclically-induced internal back stress. The results imply that an ice cover is the weakest and, thus, most susceptible to failure after long “quiet” periods related to the absence of ocean waves. Once ocean waves start gradually increasing, the cover is expected to become stronger and less susceptible to failure.